Clinical research and practice - Pokorski, Mieczyslaw (Springer, 2017)
This book is a blend of medical research and clinical practice. Advancements in practice are inextricably bound to have research underpinnings. The articles highlight a range of practical topics. The respiratory tract is upfront as the first line of defense of the organism. Virological and bacteriological aspects of the infections that continue to be a scourge worldwide, influenza and tuberculosis, are dealt with. Sleep disordered breathing is another hot topic. Allergy and atopy, and the role of nutraceuticals in providing anticancer benefits due to the inhibitory effects on tumor growth and angiogenesis are referred to. Other chapters describe the use of mesenchymal stem cells for regeneration of the worn away cartilage tissue in the knee. The assessment and management of cognitive decline, sarcopenia and frailty of old age also figure prominently in the texts. The book is an attempt to demonstrate the viability of a bench-to-bedside design in point-of-care patient applications. Hopefully, it will be a source of information on interdisciplinary medical research advancements, addressing the needs of medical professionals, from scientists to clinicians and allied health professionals.
Includes index.
Keywords: Clinical medicine -- Research.; elektronické knihy; electronic books